Comparison of Media Relations Strategies In The Digital And Traditional Era - Edhy Aruman; Dewi Nabila Rahmatya Irawan; Mohammad Alaric Hanedhy Edigani Putra (Ikatan Sarjana Komunikasi Indonesia, 2025)
The rapid evolution of the media landscape over the past few decades has fundamentally transformed media relations practices, creating a clear distinction between traditional and digital approaches. Traditional methods, such as press conferences and face-to-face journalist engagement, have proven effective in building trust and producing in-depth, analytical coverage. In contrast, digital platforms offer speed and wide reach through tools such as WhatsApp and email but often sacrifice relationship quality and message depth. While prior studies have examined both approaches separately, few have provided an integrated comparison within the context of a large-scale corporate event. This study addresses that research gap by evaluating how combining traditional and digital strategies can enhance organizational visibility, credibility, and media coverage. The research applies Two-Way Symmetrical Communication and Excellence Theory to assess how reciprocal dialogue and strategic communication contribute to the effectiveness of media relations. Using a qualitative descriptive approach, this study explored the MarkPlus Conference 2024 as a case study. Data were obtained through in-depth interviews with six journalists (three from print media and three from digital platforms) and the Corporate Communication Team. Analysis was conducted by categorizing results based on media type, identifying advantages and limitations, and triangulating with secondary data to ensure validity. The findings reveal that traditional approaches are more effective in building personal relationships and generating credible, in-depth coverage but demand higher resource investment. Digital strategies enable faster information distribution but struggle to maintain long-term relationships. This research provides new insights by demonstrating that integrating both approaches creates complementary advantages, supporting more effective media engagement in today’s dynamic communication environment.